2016
DOI: 10.1021/acs.jpcc.5b10624
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure of Deep Eutectic Solvents at Graphite Electrode Interfaces as a Function of Potential

Abstract: Atomic force microscopy (AFM), density functional theory (DFT) calculations, and contact angle measurements have been used to investigate the liquid–highly ordered pyrolytic graphite (HOPG) electrode interface for three deep eutectic solvents (DESs) as a function of applied potential. The DESs examined are 1:2 mixtures of choline chloride and urea (ChCl:urea), choline chloride and ethylene glycol (ChCl:ethylene glycol), and choline chloride and glycerol (ChCl:glycerol). DFT calculations reveal that in all case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 58 publications
11
63
0
Order By: Relevance
“…37,38 Beisdes, Chen et al studied the EDLS for three different DESs on a highly ordered pyrolytic graphite (HOPG) electrode as a function of the applied potential using atomic force microscopy (AFM), contact angle measurements and density functional theory (DFT). 39 Their results revealed that the DESs interfacial structure can be described as a multilayer, where the number of layers is dependent on the surface polarization and the hydrogen bonding capacity of the HBD molecule. In addition, the DFT simulations indicated that in all cases the HBD (i.e., urea, ethylene glycol and glycerol) is away from the graphite interface at all potentials.…”
Section: Toc Graphicsmentioning
confidence: 99%
“…37,38 Beisdes, Chen et al studied the EDLS for three different DESs on a highly ordered pyrolytic graphite (HOPG) electrode as a function of the applied potential using atomic force microscopy (AFM), contact angle measurements and density functional theory (DFT). 39 Their results revealed that the DESs interfacial structure can be described as a multilayer, where the number of layers is dependent on the surface polarization and the hydrogen bonding capacity of the HBD molecule. In addition, the DFT simulations indicated that in all cases the HBD (i.e., urea, ethylene glycol and glycerol) is away from the graphite interface at all potentials.…”
Section: Toc Graphicsmentioning
confidence: 99%
“…However, DESs are usually less toxic, easier to prepare, and less expensive than ILs. These advantages have led to the recent increase in applications of DESs, for example, as solvents in diverse separation methods [4][5][6][7][8], media for chemical [9][10][11][12][13][14], electrochemical [15][16][17][18][19], and biological reactions [20,21], in polymer chemistry [22][23][24], and for increasing the solubility of active pharmaceutical ingredients [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Negative values of ΔG rxn can be used to indicate the thermodynamically feasibility. Previously, B3LYP and M062X have been used in the simulation of ChCl based DESs [31][32][33][34]. In Table 1, ΔG rxn values of easily obtained DESs were lower than 0, according to the ΔG rxn results of B3LYP (ΔGB3LYP rxn).…”
Section: Synthesis Of Dessmentioning
confidence: 98%